2014
DOI: 10.5194/nhess-14-2409-2014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synoptic conditions for tornadic days over western Greece

Abstract: Abstract.Tornadoes have been reported in Greece during the last few decades and recent studies have given evidence that western Greece is an area vulnerable to tornadoes, waterspouts and funnel clouds In this study, the composite means and anomalies of synoptic conditions for tornadic events (tornadoes, waterspouts and funnel clouds) over western Greece are analyzed and discussed.The daily composite means of synoptic conditions were based on the National Centers for Environmental PredictionNational Center for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
5
1
1
Order By: Relevance
“…Sioutas () found that the short‐wave trough pattern is the most common synoptic pattern on waterspout days, followed by the closed low pattern. However, research by Nastos and Matsangouras (, ) and Matsangouras et al () over different geographical areas of Greece showed that waterspouts and tornadoes in Greece are reported for a variety of different synoptic conditions. Thus, an objective synoptic classification based on regional clustering of the waterspout and tornado events is necessary in order to interpret synoptic conditions that favour waterspout and tornado development over a specific geographical area.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sioutas () found that the short‐wave trough pattern is the most common synoptic pattern on waterspout days, followed by the closed low pattern. However, research by Nastos and Matsangouras (, ) and Matsangouras et al () over different geographical areas of Greece showed that waterspouts and tornadoes in Greece are reported for a variety of different synoptic conditions. Thus, an objective synoptic classification based on regional clustering of the waterspout and tornado events is necessary in order to interpret synoptic conditions that favour waterspout and tornado development over a specific geographical area.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings of prevailing northwesterly winds at 500 hPa are in agreement with Matsangouras et al (), who showed that a very broad trough at 500 hPa was located over the Aegean Sea, resulting in W–NW upper air flow over Crete on autumn waterspout days during the period covering 1 September 1948–31 December 2012. However, the occurrence of northwesterly winds that favoured waterspout activity during the autumn season, at middle and lower levels of the troposphere over the southern Aegean Sea, differs from the SW upper and lower air flow that favours waterspout activity over western Greece (Nastos and Matsangouras, ). Northwesterly winds in autumn at 850 and 925 hPa are consistent with a shallow, cyclonic circulation over the SE Aegean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura, diversos estudos têm sido realizados a fim de compreender e identificar o ambiente em que tempestades geradoras de tornados se desenvolvem. Alguns estudos mostram que tornados podem se formar no setor quente de sistemas frontais (Nastos;Matsangouras, 2014;Wrona;Avotniece, 2015;Tochimoto;Niino, 2016). Nestes estudos, os autores observaram características semelhantes nas condições atmosféricas de grande escala nas quais as formações tornádicas analisadas ocorreram.…”
Section: Introductionunclassified
“…Keul et al (2009), Sioutas and Keul (2007), and Matsangouras et al (2014b) presented a spatial and temporal analysis of waterspout thermodynamic characteristics over the Ionian, and the Aegean Sea. Moreover, specific synoptic types favouring waterspout formation over the northern Ionian Sea were classified by Matsangouras et al (2013), and an analysis of composite synoptic conditions relating to tornado and waterspout formation over western Greece was carried out by Matsangouras (2012, 2014). Based on the abovementioned tornado database, a systematic scientific research project is in progress at LACAE, analyzing significant tornado case studies, numerical simulations, and investigating the contribution of Greek complex topography in tornadogenesis (e.g.…”
Section: Introductionmentioning
confidence: 99%